Web-based medical image retrieval system - Dimitrovski, Ivica; Gjorgjevikj, Dejan; Loshkovska, Suzana (My University, 2007)
Among the applications of computer science in the field of medicine, the processing of medical image data is playing an increasingly important role. With medical imaging techniques such as X-Ray, computer tomography, magnetic resonance imaging, and ultrasound, the amount of digital images that are produced in hospitals is increasing incredibly fast. Thus the need for systems that can provide efficient retrieval of images of particular interest is becoming very high. The two different approaches used for the representation of images are: the metadata-based and the content-based approaches. For very large database personally describing and annotating every image with text indices is time-consuming and impractical. In this paper we propose a content-based image retrieval system with parallel retrieval engines to achieve higher retrieval performance and efficiency.